Word becomes image : openwork vessels as a reflection of late antique transformation - Meredith, Hallie, 1976- (Archaeopress archaeology., 2015)
This study presents a diachronic investigation providing a rich case study as well as an approach tracing the contours of a category of Roman material culture defined by the Roman period technique of openwork carving. As the first comprehensive assemblage of openwork vessels from Classical to late Antiquity, this work offers primary evidence documenting a key example of the fundamental shift from naturalism to abstraction in which inscriptions are transformed and word becomes image. A glass blower herself, Hallie Meredith poses questions about process, tactility and reception providing a clear picture of the original contexts of production and reception demonstrated by the Roman technique of openwork carving.